2020
DOI: 10.18203/2320-1770.ijrcog20205249
|View full text |Cite
|
Sign up to set email alerts
|

Doppler study (cerebroplacental ratio) as a predictor of adverse perinatal outcome

Abstract: Background: Objective of the current study was to determine the importance of Doppler screening (cerebroplacental ratio i.e. CPR) in antenatal mothers and its effect on perinatal outcome of the baby so that appropriate management can be planned effectively for a better reduction in perinatal mortality and morbidity.Methods: A prospective study conducted on hundred antenatal women in GMKMCH, Salem with gestational age >32 weeks, with singleton pregnancies. Doppler ultrasonogram of fetal middle cerebral arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
2
2
Order By: Relevance
“…This result agrees with Dall'Asta et al [14] who found that obstetric intervention for suspected fetal distress in labor was frequently higher among cases with reduced CPR MoM compared to cases with normal CPR MOM [9/54 [16.7%] vs 28/508 [5.5%]; P = 0.001. Similarly, Sengodan and Mathiyalagan [20] found that 25 babies out of 100 full term uncomplicated pregnancy that had CPR<1, 18 of them were delivered by CS and only 7 of them were delivered vaginally [spontaneous vaginal delivery]. We found that was a significant negative correlation between the rate of emergency CS due to Fetal distress and abnormal CPR, r=-0.293, p=0.001.…”
Section: Discussionsupporting
confidence: 62%
“…This result agrees with Dall'Asta et al [14] who found that obstetric intervention for suspected fetal distress in labor was frequently higher among cases with reduced CPR MoM compared to cases with normal CPR MOM [9/54 [16.7%] vs 28/508 [5.5%]; P = 0.001. Similarly, Sengodan and Mathiyalagan [20] found that 25 babies out of 100 full term uncomplicated pregnancy that had CPR<1, 18 of them were delivered by CS and only 7 of them were delivered vaginally [spontaneous vaginal delivery]. We found that was a significant negative correlation between the rate of emergency CS due to Fetal distress and abnormal CPR, r=-0.293, p=0.001.…”
Section: Discussionsupporting
confidence: 62%
“…9 According to Subha S and Sankari M, the route of birth was LSCS in 64%, and the mean age was 24.9 years whereas in the present study LSCS rate was lower (38.9%). 10 According to Subha et al, 52% were primigravidae (78.8% in the present study) and 70% had gestational hypertension whereas in our study only 17.7% had hypertensive disorders of pregnancy. 10 Cerebroplacental ratio was not found to be useful in the investigation by Vollgraff et al in predicting any negative perinatal outcome.…”
Section: Discussioncontrasting
confidence: 43%
“…10 According to Subha et al, 52% were primigravidae (78.8% in the present study) and 70% had gestational hypertension whereas in our study only 17.7% had hypertensive disorders of pregnancy. 10 Cerebroplacental ratio was not found to be useful in the investigation by Vollgraff et al in predicting any negative perinatal outcome. 11 In the present study 26.9% of women were delivered before 36weeks which concurred with a study by Dall'asta et al {n=562}, in which women with reduced CPR MoM delivered at an early gestational age.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…There is a substantial variation in the groups in term of low APGAR, fetal distress, meconium aspiration, hypoxic ischemic encephalopathy and NICU admission. The weight at birth of the newborns, the Apgar score at 1 and 5 minutes, the need for admittance to the NICU, the length of stay in the NICU, and perinatal mortality were all examined in Sengodan and Mathiyalagan's, 19 research.…”
Section: Resultsmentioning
confidence: 99%